2007
DOI: 10.4067/s0716-10182007000300002
|View full text |Cite
|
Sign up to set email alerts
|

Evidencia clínica y serológica de rickettsiosis canina en Chile

Abstract: This is the first evidence of canine rickettsiosis in Chile, both clinical and serological. Co-infection with two tickborne agents: Rickettsia and Anaplasma, is documented. Molecular studies are needed to confirm the rickettsial species present in Chile. The zoonotic role of these infections must be also studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
5
0
2
Order By: Relevance
“…Until this report, there was very limited information of human rickettsial disease in Chile, with one exception in the early 20th century [24]. However, there is serological evidence of rickettsial infections in domestic animals, ticks, and fleas [12,13]. A study on domestic cats identified fleas infected with R. felis [7,13], which may implicate this agent as the cause of the Chilean outbreak, particularly as there is serological cross-reactivity between R. conorii and R felis antigens [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until this report, there was very limited information of human rickettsial disease in Chile, with one exception in the early 20th century [24]. However, there is serological evidence of rickettsial infections in domestic animals, ticks, and fleas [12,13]. A study on domestic cats identified fleas infected with R. felis [7,13], which may implicate this agent as the cause of the Chilean outbreak, particularly as there is serological cross-reactivity between R. conorii and R felis antigens [25].…”
Section: Discussionmentioning
confidence: 99%
“…In Chile, no human case of rickettsial infection has been reported. However, there is serological evidence of rickettsial infections in dogs [12] and the cat flea has been identified as the reservoir [13]. There is also evidence of rickettsial species in ticks; however the pathogenicity of these agents is currently unknown [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical variables collected in the physical examination included vaccination (yes or no, without quantifying the number or type of vaccine, according to the information provided by the owners); antiparasitic treatments against ectoparasites and endoparasites, applied anytime in the 3 months before the day of the physical examination (yes or no, regardless of the doses or commercial brands, according to the information provided by the owners); fever (no (≤39 °C) or yes (>39 °C) by the use of a thermometer via the rectum); hemorrhages and epistaxis (no or yes if any sign in the skin or the mucosa, including oral, conjunctival, perianal and vulval in females); body condition (skinny; below 20% of the ideal body condition, ideal and overweight, regarding the breed [ 23 ]); skin lesions (no or yes if present in any body site, regardless of severity and distribution); bruising, petechiae and ecchymoses (no or yes, including oral mucosa, conjunctiva, perianal and vulvar mucosa in females); and other clinical signs such as nervous and locomotor disorders (yes or no) compatible with Rickettsia infection as previously described [ 24 , 25 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…En Chile, este complejo de especies se distribuye desde Arica en el extremo norte (18 °29′01 "S) hasta Valdivia en el sur (39 ° 49′11" S) 17,18 , siendo el último antecedente a nivel nacional documentado por Oyarzún-Ruiz y cols., (2021) que demostró su presencia en Osorno (Región de los Lagos) 19 . Anteriormente, Díaz y cols., (2018), demostraron una distribución más amplia para el linaje tropical, abarcando hasta la latitud 22°S en Chile (Argentina, 23°S; Paraguay, 25°S; Brasil, 28°S).…”
Section: Zoonosisunclassified